Sex Determinasi pada Manusia dan Karakteristik Sex yang Terikat - Anjani, Arum Dwi; Aulia, Devy Lestari Nurul (Universitas Batanghari Jambi, 2025)
In this study, the purpose of this study was to deepen information about sex determination, especially sex determination in humans. The research method used is the literature review method by utilizing several sources, both national and international journals related to relevant research results on